Literature Review: The Influence of Forensic Audit, Investigative Audit, and Auditor Independence on Fraud Disclosure - Sitorus, Atikah Zuhra; Aliyah, Dini Rahma; Br. Bangun, Mudtiani Hakim; Lubis, Nurmala Sari; Azzahra, An Suci (Indonesian Journal Publisher, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG) on company financial performance. GCG functions as a system that regulates and manages companies to create added value for all stakeholders. The method used is qualitative with a literature study approach, collecting and analyzing various academic sources and related publications. The results of the study indicate that the board of directors has a positive and significant influence on the financial performance of companies. Meanwhile, the influence of independent commissioners and managerial ownership shows mixed results, and the influence of the audit committee on financial performance tends to be inconsistent, with some studies finding no significant influence. Overall, the effective implementation of GCG is crucial for improving a company's financial performance and attracting investor attention. The conclusion of this study emphasizes that the optimal application of GCG principles can be a key factor in strengthening a company's financial performance and competitiveness in the market